2017
DOI: 10.1108/jaee-05-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

The extent of voluntary corporate disclosure in the Egyptian Stock Exchange

Abstract: Purpose The purpose of this paper is to investigate the current level of voluntary corporate disclosure in the Egyptian Stock Exchange. In addition, it explores the factors influencing the extensiveness of voluntary disclosure and examines the potential consequences of such disclosure in regards to the phenomenon of earnings management. Design/methodology/approach A relevant disclosure index to the Egyptian context was adopted to assess the level of voluntary disclosure in the 2010 annual reports of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 85 publications
(138 reference statements)
3
36
5
3
Order By: Relevance
“…Hasil ini sejalan dengan tidak adanya pengaruh signifikan profitabilitas terhadap kualitas pengungkapan laporan keuangan dinyatakan oleh Jouirou dan Bechir (2014), Modarres, Alimohamadpour, dan Rahimi (2014), Dawd (2015), Appiah, K. O., Awunyo-Vitor, D., Mireku, K., dan Ahiagbah (2016), Awadallah (2017.…”
Section: Uji Tunclassified
See 2 more Smart Citations
“…Hasil ini sejalan dengan tidak adanya pengaruh signifikan profitabilitas terhadap kualitas pengungkapan laporan keuangan dinyatakan oleh Jouirou dan Bechir (2014), Modarres, Alimohamadpour, dan Rahimi (2014), Dawd (2015), Appiah, K. O., Awunyo-Vitor, D., Mireku, K., dan Ahiagbah (2016), Awadallah (2017.…”
Section: Uji Tunclassified
“…Entitas mampu mengeluarkan biaya-biaya dalam penyusunan laporan keuangan tahunan dibandingkan harus mengeluarkan biaya agensi atau menggunakan jasa orang lain (Modarres et al, 2014). Pembuktian ini selaras dengan Barako et al (2006), Juhmani (2013, Soliman (2013), Jouirou dan Bechir (2014), Modarres et al (2014), Awadallah (2017. Hal yang mendasari alasan adanya pengaruh signifikan adalah entitas cenderung mempunyai biaya keagenan besar karena jika ukuran perusahaan makin besar maka jumlah pemangku kepentingan semakin meningkat untuk keterlibatan dalam perusahaan (Suta & Laksito 2012).…”
Section: Uji Tunclassified
See 1 more Smart Citation
“…This overwhelming appeal of corporate voluntary disclosure creates ample research opportunities in academic research over the years. Indeed, corporate voluntary disclosure becomes an enduring and vibrant aspect of the corporate reporting landscape in the last couple of years (Cotter et al, 2011;Kamel & Awadallah, 2017;Kolsi, 2017;Zaini et al, 2018). Business organizations have to disclose a minimum level of information in a competitive business environment, which is accredited as mandatory disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that big US audit firms ensure audit quality, and that companies audited by big firms have lower insurance payouts than those audited by small audit firms (Habbash, 2010). Due to the need for strong corporate governance, codes and practices guidelines have recently been drawn up by some countries, especially due to increased concerns over integrity in the securities markets (Kamel and Awadallah, 2017). Investor confidence is determined by the level and quality of corporate governance imparted by the board of directors, which greatly influence financial reporting (Adams and Mengistu, 2008;Adeyemi and Fagbemi, 2010).…”
Section: Introductionmentioning
confidence: 99%